Texture and microstructure evolution in single-phase TixTa 1-xN alloys of rocksalt structure - Abadias, Gregory; Patsalas, Panos; Koutsokeras, Loukas E. (My University, 2011)
The mechanisms controlling the structural and morphological features (texture and microstructure) of ternary transition metal nitride thin films of the TixTa1-xN system, grown by various physical vapor deposition techniques, are reported. Films deposited by pulsed laser deposition, dual cathode magnetron sputtering, and dual ion beam sputtering have been investigated by means of x-ray diffraction in various geometries and scanning electron microscopy. We studied the effects of composition, energetic, and kinetics in the evolution of the microstructure and texture of the films. We obtain films with single and mixed texture as well as films with columnar zone-T and globular type morphology. The results have shown that the texture evolution of ternary transition metal nitrides as well as the microstructural features of such films can be well understood in the framework of the kinetic mechanisms proposed for their binary counterparts, thus giving these mechanisms a global application
Keywords: Titanium nitride; Magnetron sputtering; Ion plating